2003
DOI: 10.1074/jbc.m302706200
|View full text |Cite
|
Sign up to set email alerts
|

Mice with Targeted Mutation of Peroxiredoxin 6 Develop Normally but Are Susceptible to Oxidative Stress

Abstract: Prdx6؊/؊ macrophages had higher hydrogen peroxide levels, and lower survival rates; Prdx6 ؊/؊ mice had significantly lower survival rates, more severe tissue damage, and higher protein oxidation levels. Additionally, there were no differences in the mRNA expression levels of other peroxiredoxins, glutathione peroxidases, catalase, superoxide dismutases, thioredoxins, and glutaredoxins between normal Prdx6 ؊/؊ and Prdx6 ؉/؉ mice and those injected with paraquat. Our study provides in vivo evidence that PRDX6 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
249
1
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(270 citation statements)
references
References 50 publications
15
249
1
5
Order By: Relevance
“…PRDX6 protein expression was comparable in lenses/LECs of both groups and a similar finding has been reported by other groups. 43 Accordingly, we utilized wild-type mice and homozygous lenses/LECs throughout the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…PRDX6 protein expression was comparable in lenses/LECs of both groups and a similar finding has been reported by other groups. 43 Accordingly, we utilized wild-type mice and homozygous lenses/LECs throughout the study.…”
Section: Resultsmentioning
confidence: 99%
“…10 Recently, using Prdx6 À/À mouse, it has been reported that endogenously produced mouse PRDX6 functioned in vivo as an antioxidant enzyme, and its function was not redundant to other PRDXs and antioxidant enzyme. 43 Notably, the gene expression of Prdx1-5, Gpx1-4, Cat, superoxide dismutase (Sod1-3), thioredoxin (Txn1-2), and Glutaredoxin (Glrx1-2) was found similar between Prdx6 À/À and Prdx6 þ / þ mice. 43 These findings suggest that PRDX6 activities are independent of other enzymes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The two proteins, DJ-1 and PRDX6, act against oxidative stress: DJ-1 as a quencher for ROS (Junn et al, 2005) and PRDX6 as a catalyser of the H 2 O 2 reduction (Wang et al, 2003). ROS-driven oxidative stress influences many biological processes, including cell survival and death.…”
Section: Protein Involved In Oxidative Resistancementioning
confidence: 99%